Designs of Singlet Fission Chromophores with a Diazadiborinine Framework. Issue 11 (21st July 2020) - Pradhan, Ekadashi; Bentley, Jordan N.; Caputo, Christopher B.; Zeng, Tao
Abstract: In 2016, a diazadiborinine molecule was synthesized ( Nature Commun . 2016, 7, 11871). The core structure of this molecule is a 6‐membered π system with a trans stitching up of two NCB fragments. This core structure is identical to a model singlet fission chromophore that one of us (T.Z.) proposed in 2014 ( J. Am. Chem. Soc . 2014, 136, 12638–12647.) Inspired by this resemblance, we performed quantum chemistry calculations to design a series of singlet fission chromophores based on the diazadiborinine framework. The essence is to impair the aromaticity of the diazadiborinine framework by substitutions and/or additions so that diradical resonance structures gain higher weight in the ground states of the designed chromophores. Abstract : By running quantum chemistry calculations, we proposed a series of singlet fission chromophores based on the diazadiborinine framework shown in the figure. Exocyclic substitutions of π donors and/or acceptors at the designated sites were found to make the molecules satisfy the energy criteria of singlet fission. Hydrogen addition of the olefinic moieties in the 5‐membered side rings and the replacement of the NMe by CH2 also led to singlet fission chromophores.